(untitled) (Journal of Hama University, 2024)
Abstract Thesis nutrition is one of the basic pillars on which any animal husbandry project is based. Given the high costs of feed and to improve its utilization and raise the production of breeding stock, many food additives have been used due to their positive impact on production, but some of these additives have begun to be used in feeds, raising concerns about their negative effects on production. Human and animal health, such as antibiotics, as some germs may be resistant to these antibiotics, so alternatives to them have been searched for. Among these additives that may constitute a good alternative is zeolite, which is one of the types of clay minerals that are widespread in nature and is mainly composed of aluminum silicates. Its use has had positive effects on production, while maintaining the health status of the herd and its physiological parameters within natural limits. The use of yeast also indicated... Their effectiveness in improving production and improving the digestion of nutrients, and due to the abundance of these additives and their low prices, they can constitute a good alternative to traditional additives such as antibiotics.